Genome Sequence Variations of Infectious Bronchitis Virus Serotypes From Commercial Chickens in Mexico - Kariithi, Henry M.; Volkening, Jeremy D.; Leyson, Christina M.; Afonso, Claudio L.; Christy, Nancy; Decanini, Eduardo Lucio; Lemiere, Stéphane; Suarez, David L. (Frontiers in Veterinary Science, 2022)
New variants of infectious bronchitis viruses (IBVs; Coronaviridae) continuously emerge despite routine vaccinations. Here, we report genome sequence variations of IBVs identified by random non-targeted next generation sequencing (NGS) of vaccine and field samples collected on FTA cards from commercial flocks in Mexico in 2019–2021. Paired-ended sequencing libraries prepared from rRNA-depleted RNAs were sequenced using Illumina MiSeq. IBV RNA was detected in 60.07% (n = 167) of the analyzed samples, from which 33 complete genome sequences were de novo assembled. The genomes are organized as 5'UTR-[Rep1a-Rep1b-S-3a-3b-E-M-4b-4c-5a-5b-N-6b]-3'UTR, except in eight sequences lacking non-structural protein genes (accessory genes) 4b, 4c, and 6b. Seventeen sequences have auxiliary S2' cleavage site located 153 residues downstream the canonically conserved primary furin-specific S1/S2 cleavage site. The sequences distinctly cluster into lineages GI-1 (Mass-type; n = 8), GI-3 (Holte/Iowa-97; n = 2), GI-9 (Arkansas-like; n = 8), GI-13 (793B; n = 14), and GI-17 (California variant; CAV; n = 1), with regional distribution in Mexico; this is the first report of the presence of 793B- and CAV-like strains in the country. Various point mutations, substitutions, insertions and deletions are present in the S1 hypervariable regions (HVRs I-III) across all 5 lineages, including in residues 38, 43, 56, 63, 66, and 69 that are critical in viral attachment to respiratory tract tissues. Nine intra-/inter-lineage recombination events are present in the S proteins of three Mass-type sequences, two each of Holte/Iowa-97 and Ark-like sequence, and one each of 793B-like and CAV-like sequences. This study demonstrates the feasibility of FTA cards as an attractive, adoptable low-cost sampling option for untargeted discovery of avian viral agents in field-collected clinical samples. Collectively, our data points to co-circulation of multiple distinct IBVs in Mexican commercial flocks, underscoring the need for active surveillance and a review of IBV vaccines currently used in Mexico and the larger Latin America region.